Ben Affleck & Matt Damon : 6 action movies the spy killer ; Phantoms ; The road killers ; Gerry ; Existenz ; Tom Clancy's Netforce. - Horton, Robert, 1924-2016.; Cabot, Sebastian; St. John, Jill.; Affleck, Ben, 1972-; Schreiber, Liev.; O'Toole, Peter, 1932-2013.; Affleck, Casey, 1975-; Lambert, Christopher, 1957-; Sheffer, Craig, 1960-; Brolin, Josh.; Gordon-Levitt, Joseph, 1981-; Arquette, David; et al. ([United States] : Miramax : Echo Bridge Home Entertainment, 2013)
The spy killer: Once a secret agent, John Smith decides to pursue a career as a private investigator. Now he's being framed for murder and his former boss bails him out ... with certain conditions attached.
Phantoms: Five lone survivors of a town must stop a terrifying force of evil before it totally wipes out mankind.
The road killers: The horrifying story of a young boy almost runover by a maniac on a highway and the escalation of violence as the gang's leader orders murder and kidnapping.
Gerry: A pair of best friends set out on a desert hike. Soon the daytime adventure turns into an intense life-and-death journey.
Existenz: At a demonstration of a virtual game, its designer is attacked and real world dangers merge with fantasy.
Tom Clancy's Netforce: A division of the FBI, called "NetForce" has been initiated to investigate Internet crime. When their commander is murdered, the team uncovers a character who has found a loophole in his new web browser that enables him to gain control of the Internet.
The spy killer -- Phantoms -- The road killers -- Gerry -- Existenz -- Tom Clancy's Netforce.
Title from container.
The spy killer: Director, Roy Ward Baker ; story from the novel by Jimmy Sangster.
Phantoms: Directed by Joe Chappelle ; screenplay by Dean Koontz.
The road killers: Directed by Deran Sarafian ; written by Tedi Sarafian.
Gerry: Screenplay by Casey Affleck, Matt Damon, Gus Van Sant ; directed by Gus Van Sant.
Existenz: Written and directed by David Cronenberg.
Keywords: Feature films; Film adaptations